Low-Carbon Power Engineering in the Russian Border Regions of Siberia and the Far East: An Analysis of Household Potential - Klevakina, Ekaterina A.; Zabelina, Irina A.; Shvorina, Ksenia V.; Yakovleva, Ksenia A. (International Journal of Energy Economics and Policy, 2017)
The main purpose of this paper is to present the results of the analysis of the use of individual solar stations by households in the eastern part of Russia. The population of the eastern Russian regions was surveyed on the attitude towards the use of alternative energy sources and it was made an attempt to define whether it is appropriate to use them in individual households. The article uses colors of growth framework, which is used in the process of analyzing power engineering development in the regions in question. It was found that in most regions of the Russian Far East energy sector development brings about air pollution, i. e., economic result increase is associated with the enhancement of general and specific environmental impact on the atmospheric air. Consequently, large-scale use of solar energy by households can significantly reduce emissions to the atmosphere. The article also outlines the main tasks, the solution of which will promote the spread of renewable energy use in the regions of Russia. Keywords: green energy; colors of economic growth; solar energy; willingness to pay; eco-intensity; Russia. JEL Classifications: Q5, R5, L94, Q42